PLEASURE AND POSITIVE EMOTION IN MARKETING - Nolan Keane Simon (Insains Institute, 2023)
This study aims to determine the effect of product information, pleasure and visual merchandising on purchasing decisions with positive emotions as a mediating variable in the Diecaster Community. Based on the results of research conducted using Structural Equation Modeling (SEM) processed with AMOS shows that product information has a positive impact on purchasing decisions. Pleasure has a positive effect on purchasing decisions. Visual merchandising has a positive impact on purchasing decisions. Positive emotions has a positive impact on purchasing decisions. Positive emotions mediate the impact of product information on purchasing decisions. Positive emotions can mediate pleasure on purchasing decisions. Positive emotions cannot mediate visual merchandising on purchasing decisions. Positive emotions cannot mediate visual merchandising on purchasing decisions.